Pengaruh Penilaian Kinerja dengan ROI dan EVA terhadap Return Saham pada Perusahaan yang Tergabung dalam Indeks LQ 45 di Bursa Efek Indonesia - Harjono Sunardi (Jurnal Akuntansi)
There have been many investors who invest funds in certain companies. The purpose of the investment is to obtain the expected stock return. Investors, in investing certainly needs to look at whether the company will be turned into investment activity to perform well or not, because only companies that have good performance that can provide the expected stock return.